2018
DOI: 10.5194/acp-18-1785-2018
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of individual ice residual particles by the single droplet freezing method: a case study in the Asian dust outflow region

Abstract: Abstract. In order to better characterize ice nucleating (IN) aerosol particles in the atmosphere, we investigated the chemical composition, mixing state, and morphology of atmospheric aerosols that nucleate ice under conditions relevant for mixed-phase clouds. Five standard mineral dust samples (quartz, K-feldspar, Na-feldspar, Arizona test dust, and Asian dust source particles) were compared with actual aerosol particles collected from the west coast of Japan (the city of Kanazawa) during Asian dust events i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

10
35
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(45 citation statements)
references
References 97 publications
10
35
0
Order By: Relevance
“…Similar to 25 quartz, calcium containing particles showed different ice nucleation ability in previously laboratory studies (Zimmermann et al, 2008;Atkinson et al, 2013). In field experiments, however, Ca-rich particles and Ca-sulphates were observed in the IPR fraction (Ebert et al, 2011;Worringen et al, 2015;Iwata and Matsuki, 2018).…”
supporting
confidence: 51%
See 4 more Smart Citations
“…Similar to 25 quartz, calcium containing particles showed different ice nucleation ability in previously laboratory studies (Zimmermann et al, 2008;Atkinson et al, 2013). In field experiments, however, Ca-rich particles and Ca-sulphates were observed in the IPR fraction (Ebert et al, 2011;Worringen et al, 2015;Iwata and Matsuki, 2018).…”
supporting
confidence: 51%
“…Laboratory studies (Atkinson et al, 2013;Iwata and Matsuki, 2018) showed that K-feldspar and clay minerals (Zimmermann et al, 2008;Hiranuma et al, 2015;Boose et al, 2016) have a high ice nucleation ability compared to other minerals. A high ice 20 nucleation ability of clay minerals is also reported from field experiments (Targino et al, 2006;Worringen et al, 2015).…”
mentioning
confidence: 99%
See 3 more Smart Citations